An analytic cross-sectional study of Somali women on the sexual and psychosocial status during pregnancy - Adil Barut; Samira Ahmed Mohamud; Umut Erkok; Ifrah Salad Hassan (BMC, 2024)
Abstract Background Pregnancy is associated with physical, psychological, hormonal, and social alterations that may lead to detrimental effects on sexual function and psychological well-being. This study sought to examine sexual function and psychosocial well-being of pregnant women in Somalia in comparison with their non-pregnant counterparts. Methods We enrolled 487 consecutive women in monogamous marriages. Data included maternal age, gravida, parity, gestational week, education status of wives and husbands, and residence area. The participants completed the Female Sexual Function Index (FSFI) and the Brief Symptom Inventory-18 (BSI-18). Results Of 487 women, 241 were pregnant, and 246 were non-pregnant. The overall incidence of sexual dysfunction was 57.7%, being 64.0% for pregnant and 51.6% for non-pregnant women (p = 0.010). Pregnant women exhibited significantly lower FSFI scores on desire, arousal, lubrication, and orgasm, and significantly higher total BSI, anxiety, depression and somatization scores. The frequencies of sexual dysfunction were 57.9%, 45.9%, and 78.9% during the first, second, and third trimesters, respectively (p = 0.0001). As compared with the first and second trimesters, and non-pregnancy, the third trimester of pregnancy was associated with a significantly lower total FSFI score and significantly decreased levels of desire, arousal, lubrication, and orgasm, as well as a significantly higher total BSI score and a significantly increased level of anxiety. In regression analysis, pregnancy was inversely associated with sexual function parameters of desire, arousal, lubrication, and orgasm, and with BSI parameters of depression, anxiety and somatization. Conclusion Our findings suggest that pregnant women experience considerable sexual and psychosocial deterioration as compared with their non-pregnant counterparts.